Differences in stroke technique to exert hand propulsion between advanced and intermediate swimmers - Kudo, S.; Matsuda, Y.; Sakurai, Y.; Ichikawa, H.; Ikuta, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to investigate differences in hand propulsion exerted by advanced and intermediate swimmers during insweep and upsweep phases in the front crawl stroke. Swimmers wore pressure sensors on their hands while performing the front crawl stroke in the swimming pool where a motion capture system was set up. The hand propulsive drag (PD) and lift (PL) were estimated during the two phases. The advanced swimmers exerted more PD than PL (70% vs 30%) during the insweep phase and used a similar amount of PD to PL in the upsweep phase. The intermediate swimmers used a similar amount of PD to PL in the insweep phase and exerted more PD than PL in the upsweep phase (65% vs 35%). The advanced swimmers used the different technique to exert hand propulsion in the two phases as compared to the intermediate ones.